2016
DOI: 10.17980/2016.1
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic roles of epithelial and immune cell signaling during the development of colitis-associated cancer

Abstract: To date, substantial evidence has shown a significant association between inflammatory bowel diseases (IBD) and development of colitis-associated cancer (CAC). The incidence/prevalence of IBD is higher in western countries including the US, Australia, and the UK. Although CAC development is generally characterized by stepwise accumulation of genetic as well as epigenetic changes, precise mechanisms of how chronic inflammation leads to the development of CAC are largely unknown. Preceding intestinal inflammatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 148 publications
(151 reference statements)
0
26
0
Order By: Relevance
“…Based on our in vivo and in vitro results, K284-6111 inhibits NF-κB and ERK signaling. [62]. In addition, we observed that p-IκBα was inhibited when the ERK inhibitor was treated, however, p-ERK was not changed when the NF-κB inhibitor was treated.…”
Section: Discussionmentioning
confidence: 73%
“…Based on our in vivo and in vitro results, K284-6111 inhibits NF-κB and ERK signaling. [62]. In addition, we observed that p-IκBα was inhibited when the ERK inhibitor was treated, however, p-ERK was not changed when the NF-κB inhibitor was treated.…”
Section: Discussionmentioning
confidence: 73%
“…He et al demonstrated that CHI3L1 binds to IL-13Rα2 and induces ERK, AKT, and Wnt/β-catenin signals independent of IL-13 pathway [ 63 ]. Subramaniam et al described in their review paper that CHI3L1 binds to RAGE (receptor for advance glycation end product), resulting in the activation of the NF-κB, β-catenin, and MAPK signaling pathways [ 64 ]. In addition, we observed that p-IκBα was inhibited when the ERK inhibitor was treated; however, p-ERK was not changed when the NF-κB inhibitor was treated.…”
Section: Discussionmentioning
confidence: 99%
“…CHI3L1 has the ability to bind RAGE (receptor for advance glycation end product) which contributes to various cellular responses with enhanced activation of NF-κB, MAPK, and β-catenin signaling pathways [ 32 ]. NF-κB has been well documented in decreasing transcription factors regulating β-secretase in brain cells, resulting in neuronal cell death with accumulation of Aβs [ 11 ].…”
Section: Discussionmentioning
confidence: 99%